Intranet - Luleå University of Technology - Larsson, Andreas; Larsson, Tobias; Törlind, Peter (Luleå University of Technology, 2001)
The Division of Computer Aided Design has been announced as one of ten winners in the Intranet Design Annual, published by web guru Jakob Nielsen at Nielsen/Norman Group. In competition with over 50 nominated organizations, the division's Intranet, developed by Andreas Larsson, Tobias Larsson and Peter Törlind, reached the top ten. Nielsen has been called the "guru of webpage usability" by the New York Times, and he currently holds 60 U.S. Patents, most of them concerning web usability. The report states: “It is also notable that Luleå University of Technology made it to the top 10, despite being designed by a bunch of graduate students. Though small and lacking a lot of resources, this design team focused relentlessly on user needs and on simplifying their design through many fast iterations. Some of the Luleå features underwent up to 50 iterations before they reached their current usability level. ‘I thought my initial design for the calendar application was really easy to use - in fact, I was quite proud of it,’ says one of the developers. But, the design didn’t hold up when professors and other staff members used it, so it was changed. User needs triumphed over the designer’s initial pride. That’s the hallmark of a truly great designer. On a small budget, the way to achieve high-quality design is through fast, cheap iterations and a willingness to do what users need.”